The Development of Islamic Values in the Culture of the Samin Community in Klopodhuwur Blora - Alfina Wafiq Azizah; Armiya Nur Lailatul Izzah; Cahya Amelia Chusna (Global Education Journal, 2025)
The Samin community in Klopodhuwur, Blora, is a traditional society that upholds a noble system of values and customs harmoniously intertwined with Islamic teachings. The integration between local culture and Islamic values has created a distinctive form of religiosity characterized by simplicity, honesty, and sincerity. This study aims to explore the development of Islamic values within the life of the Samin community and the adaptation of Islamic teachings to their local wisdom. Employing a qualitative method with a descriptive-analytical approach through library research, the study examines various books, journals, and relevant literature to understand the socio-religious dynamics of this community. The findings reveal that the internalization of Islamic values among the Samin people occurs gradually and peacefully without erasing their cultural identity. Values such as honesty, simplicity, mutual cooperation, and sincerity serve as bridges of harmony between Islamic teachings and Samin traditions, demonstrating that religion and culture can coexist synergistically in fostering morality and social harmony.